A cost-effective proposal for an RFID-based system for agri-food traceability. (2018) - Ferrero, Renato; Gandino, Filippo; Montrucchio, Bartolomeo; Rebaudengo, Maurizio
Agri-food companies, operating in the packaging, storage and distribution of fruit and vegetables, need to be provided with information systems able to meet the requirements imposed by the current European regulations in terms of traceability. This paper evaluates the benefits and drawbacks of a semi-automated information management tracking system for awarehouse specialised in the fruit market. It is targeted to small and medium-sized companies, with limited financial means for investments and without technical support in their premises. These requirements are met by using a personal digital assistant (PDA) equipped with an radio frequency identification (RFID) reader: the information collected throughout the production process are locally stored in the PDA and occasionally sent to a server. In this way the proposed system does not rely neither on a widespread wireless network, nor on fixed RFID readers, which can increase automation, but need more investment and assistance.